Efficacy of Self-Management Smartphone-Based Apps for Post-traumatic Stress Disorder Symptoms: A Systematic Review and Meta-Analysis - Goreis, Andreas; Felnhofer, Anna; Kafka, Johanna Xenia; Probst, Thomas; Kothgassner, Oswald D. (Frontiers in Neuroscience, 2020)
Post-traumatic stress disorder (PTSD) symptoms are prevalent in both civilian and military service members. As the number of smartphone-based applications (apps) grows rapidly in health care, apps are also increasingly used to help individuals with subthreshold PTSD or full PTSD. Yet, if the apps are self-managed, the feasibility and efficacy of such interventions are still rather unclear in these two populations with PTSD symptoms. Hence, the present meta-analysis set out to evaluate the effect of self-management smartphone-based apps on PTSD and depressive symptoms in populations with subthreshold PTSD or full PTSD. Studies were included if they conducted randomized controlled trials or pre-post comparisons. Six studies (n = 2 randomized controlled trials) were identified for meta-analysis. In pre-post comparisons, N = 209 participants were included in the analyses. In randomized controlled trials, N = 87 participants received smartphone-based self-management interventions and N = 82 participants were in waitlist control conditions. Meta-analysis for pre-post comparisons concluded an effect of g = 0.55 (p < .001) regarding the overall reduction in PTSD symptoms (n = 6) and g = 0.45 (p < .001) for reduction in depressive symptoms (n = 5). Yet, in randomized controlled trials, no significant difference was found between app-based treatment and waitlist control groups (g = 0.09, p = .574). The duration of the interventions did not significantly influence the results. Overall, despite positive pre-post effects, current results indicate that smartphone-apps for PTSD patients are not significantly more effective than waitlist control conditions. Nevertheless, a combined smartphone and standard therapy approach may be a fruitful field for future research.